Accidental aspiration of foreign bodies in dental practice: clinical management and prevention. (19th September 2013) - Cossellu, Gianguido; Farronato, Giampietro; Carrassi, Antonio; Angiero, Francesca
<x xml:space="preserve">Abstract</x> Objective Foreign body aspiration is a possible complication of dental treatment that may result in a life‐threatening situation. The foreign body is often spontaneously ejected from the airway, but in other cases, surgical intervention is needed. Prevention, diagnostic procedures, treatment and complications are discussed. Materials and methods Three cases of aspiration of dental instruments are described: the piece was localised in the right main bronchus in two cases and in the left main bronchus in one case. Results All three cases underwent surgery (resection and bronchoscopy); in one case, the surgical attempt failed, and the foreign body was not located by radiography; it was assumed to have been expelled spontaneously. Conclusion The management of dental materials and instruments requires particular care, especially if the patient is supine or semi‐recumbent. The dentist must be able to manage emergency situations in which patients accidentally inspire or swallow dental instruments or materials during treatment. Preventive techniques must be put in place because these incidents are preventable if the correct precautions are taken.